Forecasting Migrant Remittances during the Global Financial Crisis - Mohapatra, Sanket; Ratha, Dilip (2012)
The financial crisis has highlighted the need for forecasts of remittance flows in many developing countries where these flows have proved to be a lifeline to the poor people and the economy. This note describes a simple methodology for forecasting country-level remittance flows in a manner consistent with the medium-term outlook for the global economy. Remittances are assumed to depend on bilateral migration stocks and income levels in the host country and the origin country. Changes in remittance costs, shifts in remittance channels, global exchange rate movements, and unpredictable immigration controls in the migrant-destination countries pose risks to the forecasts. Much remains to be done to improve the forecast methodology, data on bilateral flows, and high-frequency monitoring of migration and remittance flows.